Excess Power Management for Industires in Remote Areas: A Case Study of PT Pertamina EP Cepu - Donggi Matindok Field - Firmansyahrullah Firmansyahrullah (Eduvest - Journal of Universal Studies, 2026)
This study analyzes excess power management at PT Pertamina EP Cepu’s Donggi Matindok Field (DMF), where the power plant utilizes only 40% of its installed capacity, leaving 4–6 MW of excess electricity—worth approximately 33.9 billion rupiah annually—unutilized. The research aims to formulate an optimal business solution to improve power generation efficiency by monetizing this excess power. Using a mixed-method approach, primary data were collected through focus group discussions (FGD) with experts, questionnaires, and interviews, while secondary data included operational reports and technical records.The Kepner-Tregoe decision analysis identified monetizing excess electricity as the most viable improvement area, achieving the highest score of 82.5. Through Value-Focused Thinking, incorporating SWOT and PESTEL analyses, evaluation criteria and alternative solutions were developed. The Analytical Hierarchy Process (AHP), based on expert pairwise comparisons, determined that implementing a power swap scheme with PLN is the optimal solution, with a priority weight of 0.46124. This strategy enables DMF to reduce operational costs, increase revenue, and support national energy efficiency goals while ensuring business sustainability in remote operational areas..